Commercial's law relating to foreifn contributions in India - Banerje, Gautam (New Delhi, 2011)
This book is presented to the readers insofar as it deals with the new Act, namely, the Foreign Contribution (Regulation) Act, 2010 which has been brought into force from 1st May, 2011together with the Foreign Contribution (Regulation) Rules, 2011 made by the Central Government. By this Act, the earlier Foreign Contribution (Regulation) Act, 1976 and the Rules made thereunder have been repealed. While retaining some of the features of the repealed Act, the new Act has brought in many new features and concepts which make for better regulation of the receipt and utilization of foreign contributions in India. Every provision of the new Act of 2010 has been lucidly explained and wherever available, the relevant case laws have been given. The Foreign Contribution (Regulation) Rules, 2011 together with the prescribed Forms have been included. It is hoped that this fourth edition of the book will give proper insight and guidance into the provisions of the new law.
Keywords: "Foreign contribution regulation act, Law and legislation"